Pengaruh Sertifikasi Terhadap Keterampilan Guru Dalam Pembuatan Rencana Pelaksanaan Pembelajaran - Akbar, Aulia (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Effective learning activities require careful planning. When planning the learning activities to be carried out must consider a variety of variables, ranging from the determination of models, methods, tools, evaluation instruments and others in part. This is not easy, it requires extensive and in-depth knowledge in making a learning plan. However, Learning Implementation Plans (RPP) skill making is a skill that must be possessed by every teacher, especially teachers who are already certified. Certified teachers should already have four expected competencies, including: pedagogical, personal , social and professional . So that learning activities in class can run in accordance with what is desired . The purpose of this study is to obtain a picture of whether certification has an effect on teacher skills in making learning implementation plans. Adapu n method used is a survey method using a random sample of eight teachers. The instrument in this study uses scoring / points on the nine principles contained in the 2013 curriculum preparation principles. The results obtained are based on the results of the study being in the very high category. Even though the principles in formulating lesson plans are not yet fully understood. Both certified and non-certified teachers were on average 8.75 or 97.22%.